Effect of a 1-year intervention comprising brief counselling sessions and low-dose physical activity recommendations in Japanese adults, and retention of the effect at 2 years: a randomized trial - Julien Tripette; Yuko Gando; Haruka Murakami; Ryoko Kawakami; Kumpei Tanisawa; Harumi Ohno; Kana Konishi; Michiya Tanimoto; Noriko Tanaka; Hiroshi Kawano; Kenta Yamamoto; Akie Morishita; et al. (BMC, 2021)
Abstract Background In an effort to increase people's adherence to active lifestyles, contemporary physical activity (PA) guidelines now include low-dose PA. Methods PA was evaluated in 583 participants of the Nutritional and Physical Activity Intervention Study (NEXIS) cohort (30-65 years old); 349 inactive participants (MVPA, 2.7 ± 1.0 MET-h/day) were randomly assigned to the intervention or control groups, and 235 active participants participated in follow-up visits. The intervention aimed to increase MVPA and comprised five brief counseling sessions over 1 year. The 1-year target for the participant was increasing their step-count to 10,000 steps/d or +3000 steps/d, relative to the baseline score. The counseling sessions were designed to stimulate progressive changes in physical behaviors by recommendations promoting small and/or light-intensity bouts of PA. PA was measured at baseline, the end of the intervention, and 1 year after the intervention ended. Additionally, several nutrition, health, and fitness parameters were measured. Results Participants in the intervention group significantly increased their step-count from 8415 ± 1924 at baseline to 9493 ± 2575 at the end of the 1-year period. During the same period, MVPA significantly increased by 0.9 MET-h. The daily time spent in ≥ 3, ≥ 4 and ≥ 5 MET activities increased by 11, 6, and 3 min, respectively. This increase in PA remained observable 1 year after intervention concluded. The active group maintained higher physical activity levels throughout the two years. The intervention group showed smaller energy intakes at the end of the 2-year period. Significant correlations were noted between the 1-year change in MVPA and the change in resting heart rate (r =  − 0.22), and between the 2-year change in MVPA and the change in waist circumference (r =  − 0.08) and peak oxygen consumption capacity (r = 0.23) in the intervention group only. Conclusions A prolonged and progressive PA intervention promoting small bouts of light-to-moderate PA may be used in healthy, not-optimally-active people to increase PA beyond the strict period of the intervention. Further studies are necessary to understand whether low-dose PA messages can be effective in initiating a progressive increase toward larger amounts of PA. Trial registration: Clinical Trials.gov, NCT00926744, retrospectively registered.